Pengaruh Motivasi, Pengawasan, dan Budaya Kerja terhadap Produktivitas Kerja Karyawan Perusahaan Pengecoran Alumunium “Sp” Yogyakarta - Umi Latifah; Sri Haryani (Telaah Bisnis, 2016)
AbstractThis study aims to analyze the influence of motivation, supervision, and work culture either partially or simultaneously on employee productivity. Total population is 114 employees at the production division of aluminum casting company “SP“ Yogyakarta. By using the method of Isaac and Micheal, with a 5 % error level, sample size is 86. The sampling method used disproportionate stratified random sampling, which is a technique used to determine the number of samples when stratified population less than the proportion required. Data was analyzed using multiple regression analysis and the result states that even there is no motivation, supervision, and work culture, the employee still obtain work productivity of 7,153. All regression coefficients are positive, which mean that three variables have positive effect on labor productivity . Furthermore, it is indicated that partially,motivation and supervision do nothave any influence on employee productivity, but work culture variable does. Based on F test, variables ofmotivation,  supervision, andwork culture,simultaneously have influenced thelaborproductivity. The research also shows that 53.2% influencesof labor productivitycan be explainedbythe variables of motivation, supervision, andwork culture, while the remaining0f 46.8% is contributedbyother variablesthatis notincluded inthisstudy.